Efeito da suplementação com selênio sobre a concentração sérica de creatina kinase em bovinos - Reis, L. S. L. S. [UNESP] (2009)
The study, evaluated the addition of different concentrations of Se in mineral mixture affecting creatine kinase (CK) serum concentrations in cattle. 60 male, Nellore cattle, at about 12 months old, were randomly assigned to groups (15 calves/ group), Gc, G3,6, G5,4 or G6,4 (0, 3.6, 5.4, and 6.4 mg Se/bovine/day). The levels of serum CK in the cattle were not affected by neither the interaction selenium concentration x time nor the concentration of supplementation. However, CK levels increased over the experiment irrespective of dietary selenium concentration. In addition, the frequency of animals with CK levels above normal increased (p<0.10) in group G6,4. The concentrations of selenium studied here do not affect serum CK in cattle, but the daily concentration of 6.4 mg selenium is not recommended because it is possibly toxic effect.